The Effect of Fiscal Decentralization on the Performance of Regional Apparatus Organizations - Yustianto, Dr. Benny Prakarsa; Epenetus, Abraham Josiah; Rozika, Tara Fitria; Syarif, Arman (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study investigates the extent to which clearer and more structured fiscal decentralization regulations can reduce overlapping functions between government agencies, enhance the clarity of monitoring and evaluation mechanisms, and ultimately improve budget accountability at the regional level. In particular, the study assesses the influence of these regulatory improvements on the performance of Regional Apparatus Organizations (Organisasi Perangkat Daerah/OPD) and their institutional readiness to adapt to evolving decentralization policies and governance standards. Methodology/approach: This research adopts a literature review method, analyzing 15 previous research articles from Google Scholar and ResearchGate. The selected studies evaluate the performance of OPDs in Indonesia during the publication period from 2014 to 2024. Results/findings: Fiscal decentralization involves fund distribution and delegated authority to regions. Effective decentralization not only distributes power but also improves service quality and public participation. Evaluations should prioritize these aspects. Conlusion: Clear decentralization policies improve OPD performance and accountability but face challenges like regional disparities and limited capacity. Strengthening institutional readiness and coordination is essential. Limitations: Future research should examine specific impacts of decentralization on OPD performance and compare regions to identify influencing factors. Contribution: This study highlights trends, innovations, and challenges in fiscal decentralization, offering insights for policy reform and institutional development.